De poematum cantu et viribus rythmi - Vossius, Isaac 1618-1689 (Oxford Sheldonian Theatre, 1673)
De Poematum (On the Music of Poetry and Power of Rhythm) a work of Continental musical humanism, interesting for being published in England and dedicated to royalist Henry Bennett, Duke of Arlington. This treatise plays an important but poorly understood role in the development of rhythmopoeia; Isaac Vossius continues the arguments of figures such as Vincenzo Galilei and Marin Mersenne - desiring to link linguistic rhythm, music, and the passions - by proposing a practical, if undemonstrated, method for doing so based on ancient poetic feet. This resuscitation of poetic feet in the service of affect is made explicit first by Vossius, but is undoubtedly more familiar to musicologists from Wolfgang Caspar Printz's 1696 Phrynis Mitilenaeus or Johann Mattheson's 1739 Der vollkommene Capellmeister. Vossius, or more correctly, De poematum, was often cited during the century after its publication, and no modern treatment of rhythmopoeia seems complete without a citation or very short excerpt from this work. There is little secondary literature that focuses on this treatise, but what does exist links this work directly to John Dryden's composition of his 1687 and 1697 St. Cecilia odes, and their musical settings by Giovanni Battista Draghi and Jeremiah Clarke, respectively.
ms. note in one copy: "v. le dict. de musique de rousseau"
Ex libris Th. Palmer (ms. from 1687)Ex bibliotheca Lowell City Library (Lowell, MA) (embossed stamp)
Keywords: 17th Century (1601-1700); Linguistics; Poetry; Rhythm; Oxford (United Kingdom)